Effect of Level 1 Progressive Mobilization Therapy on Oxygen Saturation in Patients Diagnosed with Respiratory Failure in ICU of Prof. Dr. H. Aloei Saboe Hospital, Gorontalo City - Roni Mohammad A. R. Patilima; Zuhriana K. Yusuf; Nur Ayun R. Yusuf (Medical and Health Journal, 2026)
Level 1 progressive mobilization therapy is a non-pharmacological therapy using a complementary approach that can affect oxygen saturation. The purpose of this study was to determine the effect of level 1 progressive mobilization therapy on oxygen saturation in patients diagnosed with respiratory failure in the ICU of Prof. Dr. H. Aloei Saboe Regional Hospital, Gorontalo City. This study is a quantitative study with a quasi-experimental design using a one-group pre-post test design approach . which only involved one treatment group, namely the group of patients diagnosed with respiratory failure who were given level 1 progressive mobilization therapy intervention. The study population was 51 patients with an accidental sampling technique with a sample size of 45 patients. This research instrument used the SOP for level 1 progressive mobilization and an oxygen saturation observation sheet. Data analysis used the Wilcoxont-test. The results of the study obtained a p-value of 0.000 (α <0.05) meaning that there was an effect of level 1 progressive mobilization therapy on oxygen saturation in patients with respiratory failure at Prof. Dr. H. Aloei Saboe Regional Hospital, Gorontalo City. Level 1 progressive mobilization plays a crucial role in improving respiratory function, accelerating recovery, and maintaining the body's overall physiological balance. This research is expected to serve as a reference for providing nursing care, particularly level 1 progressive mobilization exercises for patients diagnosed with respiratory failure, as an effort to prevent decreased oxygen saturation.